PENEREPAN METODE ROLE PLAY DALAM MENINGKATKAN KEMAMPUAN BERBICARA DAN KUALITAS PEMBELAJARAN BAHASA INGGRIS - Azhariyah (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2020)
This study aims to improve speaking skills using and improve the quality of learning English for students X SMA Negeri 12 Takengon who are taught using the role playing method. The form of research used is Classroom Action Research. The Classroom Action Research (CAR) method used is to apply the role playing method to improve student learning outcomes in English material. Data collection techniques in the form of test questions and student activity observation sheets. The results showed that the average value of student learning outcomes in cycle I with a percentage of completeness of 53% and increased to 83% in cycle II, and 100% in the third cycle. The application of the role playing method in learning English can improve the learning outcomes of class X SMA Negeri 12 Takengon from cycle I to cycle III by 47%.